1/2 : x - 5/6 = 8/3
=> 1/2 : x = 8/3 + 5/6
=> 1/2 : x = 7/2
=> x = 1/2 : 7/2
=> x = 1/7
2 1/3 . x : 3/2 = 1 1/2
=> 7/3 . x : 3/2 = 3/2
=> 7/3 . x = 3/2 . 3/2
=> 7/3 . x = 9/4
=> x = 9/4 : 7/3
=> x = 27/28
1/5 . (x - 3/4) + 4/3 = 1 5/6
=> 1/5 . (x - 3/4) + 4/3 = 11/6
=> 1/5 . (x - 3/4) = 11/6 - 4/3
=> 1/5 . (x - 3/4) = 1/2
=> x - 3/4 = 1/2 : 1/5
=> x - 3/4 = 5/2
=> x = 5/2 - 3/4
=> x = 7/4
(5/2 - x) : 3/7 + 1,2 = 5
=> (5/2 - x) : 3/7 = 5 - 1,2
=> (5/2 - x) : 3/7 = 19/5
=> 5/2 - x = 19/5 x 3/7
=> 5/2 - x = 57/35
=> x = 5/2 - 57/35
=> x = 61/70
x - 13,27 = 1,49
=> x = 1,49 + 13,27
=> x = 14,76
23,5 + x = 40
=> x = 40 - 23,5
=> x = 16,5
3x - 15,3 = 21,9
=> 3x = 21,9 + 15,3
=> 3x = 37,2
=> x = 37,2 : 3
=> x = 12,4
7,58 + 2x = 14,6
=> 2x = 14,6 - 7,58
=> 2x = 7,02
=> x = 7,02 : 2
=> x = 3,51